Interrelation between body build variables and their velocity during puberty. (The third report of monthly-two-year investigations in Yucatan, Mexico) - Wolański, Napoleon; Rojas, Armando; Uc, Ligia; Siniarska, Anna (Studia Ecologiae et Bioethicae, 2004)
In the present, the third publication included in this volume, the main topic considers the explanation of the existence of any relations between studied variables of body builds during the period of 22 months, e.g. from the beginning till the end of investigations. At that time the considerable changes related to the pubertal period took place. The results of the correlation matrix between studied variables and factor analysis for the whole material and for each gender separately are presented. It is seen that there are differences between boys and girls in the interrelation concerning studied variables and in separated latent factors. It is rather related to differences in the phase of puberty (more advanced girls than boys in this process), although the same calendar age. Girls who mature earlier are characterized by greater initial stature and greater body weight, BM I fat mass (including subcutaneous fat tissue), and fat-free mass at the beginning and end of the study than girls who mature later. However, later matured girls show, in the whole investigated period, greater increments in stature and weight than earlier matured ones (of the same calendar age). At the earlier stage of puberty (boys under study) the factor one (F I) representing body mass and its increments, is associated with final body height (at the end of study), whereas F3 is associated with initial height (at the beginning of the study). This association is reverse at the latter phase of puberty (girls under study), while F I (also representing body mass but not its increments) is associated with the initial height, whereas final height represents the separate factor (F3).